Acceptance and Commitment-Therapy Based Counseling Group to Improve Self-Confidence of Junior High School Students - Bakhrudin All Habsy; Adelia Kusuma Sriandi; Elisabeth Christiana; Michael Adeniyi Omoyemiju (Bumi Publikasi Nusantara, 2025)
This study investigated the effectiveness of group counseling based on Acceptance and Commitment Therapy (ACT) in enhancing self-confidence among junior high school students, using a true experimental pretest-posttest control group design. Two instruments were employed: treatment and measurement. The treatment instrument consisted of a guide for implementing group counseling, while the measurement instrument was a self-confidence inventory. The findings demonstrated that ACT-based group counseling effectively enhances self-confidence among junior high school students. The study provided two recommendations: (i) for guidance and counseling teachers, ACT-based group counseling can be applied to strengthen students’ self-confidence and support their developmental understanding; and (ii) for future researchers, given that ACT-based counseling incorporates six core processes (acceptance, cognitive defusion, being present, self-as-context, values, and committed action). Future studies may explore its effectiveness with additional or alternative techniques.